Los gerundios 'analógicos' en la historia del español - Pato, Enrique; O´Neill, Paul (El Colegio de México, 2013)
The present work focuses on the documentation and distribution (historical and present day) of the so called ‘analogical’ gerunds in Spanish (tuviendo, quisiendo) on the basis of evidence from various linguisticcorpora (CORDE, CREA, Corpus del español, ALPI, and COSER). We revise previous analogical explanations of these forms and we proposean explanation for the extension of the strong preterite root to the gerund in terms of phonologically conditioned allomorphy. We also argue that our phonological explanation is more in keeping with established notions of ‘naturalness’ regarding morphological change.